2007
DOI: 10.1002/acp.1289
|View full text |Cite
|
Sign up to set email alerts
|

Does impulsivity relate to perceived dependence on and actual use of the mobile phone?

Abstract: Several authors have studied the risks arising from the growth in mobile phone use (e.g. large debts incurred by young people, banned or dangerous use of cellular phones). The aim of this study is to analyse whether impulsivity, which has often been related to various forms of addictive behaviours, is associated with massive use of and dependence on the mobile phone. In this study, 108 female undergraduate psychology students were screened using a questionnaire evaluating actual use of and perceived dependence… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
124
1
10

Year Published

2008
2008
2019
2019

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 179 publications
(146 citation statements)
references
References 23 publications
6
124
1
10
Order By: Relevance
“…In South Korea, in another study carried out with the shorter ten-item form of the SAS developed for adolescents, mean scores of female students were found to be statistically significantly higher than those of male students, just like the results of our study suggest 5 . Also, in studies on mobile phone use, problems with mobile phone use were found to be higher among females than they were among males 18,19 . Furthermore, in the study of the original scale, the SAS mean scores were found to be 104.5 in males and 112.7 in females 4 , while in our study they were found to be 72.2 in males and 78.7 in females.…”
Section: Discussionmentioning
confidence: 99%
“…In South Korea, in another study carried out with the shorter ten-item form of the SAS developed for adolescents, mean scores of female students were found to be statistically significantly higher than those of male students, just like the results of our study suggest 5 . Also, in studies on mobile phone use, problems with mobile phone use were found to be higher among females than they were among males 18,19 . Furthermore, in the study of the original scale, the SAS mean scores were found to be 104.5 in males and 112.7 in females 4 , while in our study they were found to be 72.2 in males and 78.7 in females.…”
Section: Discussionmentioning
confidence: 99%
“…In another study on British adolescents using the MPPUS the 90 th percentile was chosen to classify at risk-use according to a statistical classification they prompted to have found in pathological gambling assessment (LopezFernandez et al 2014). High prevalence rates of about 30% were reported in studies assessing addictive behaviour through a single questionnaire item ("perceived dependence") (Billieux et al 2007) or through choosing the 70 th percentile as arbitrary questionnaire cut-off value (Ha et al 2008). In our study we did not find an obvious threshold for differentiating between problematic and non-problematic mobile phone use, which supports the idea that problematic mobile phone use is a continuum and the higher the score on the MPPUS-10, the more likely mobile phone use is problematic in adolescent.…”
Section: Assessment Of Problematic Mobile Phone Usementioning
confidence: 99%
“…An earlier study by Billieux et al (2007) found that the urgency and lack of perseverance ("staying on task") dimensions of impulsivity were related to perceived cell phone dependence. The authors' 2008 study also found that the urgency dimension of impulsivity was the strongest predictor of problematic cell phone use.…”
Section: Introductionmentioning
confidence: 99%
“…Including impulsiveness in our model is also an important contribution of the present research. Behavioral addictions are often driven by the lack of impulse control (Billieux, Van Der Linden, d'Acremont, Ceschi & Zermatten, 2007;Billieux, Van Der Linden & Rochat, 2008). An additional significant contribution is the use and analysis of the Mobile Phone and Instant Messaging Scales developed by Ehrenberg et al (2008) which provides further evidence of their value in this area of research.…”
Section: Introductionmentioning
confidence: 99%